THE EFFECT OF INDEPENDENCE AND RESPONSIBILITY ON SUBORDINATE OBEDIENCE TO ENGAGE UNETHICAL BEHAVIOR: EXPERIMENTAL STUDY - Lucyanda, Jurica; Pratiwi, Monica; Tahar, Amara (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Research related to subordinate obedience to engage in unethical behavior is still limited and inconclusive because of the existence of superior pressure. Therefore, the following factors influence obedient subordinates to engage in unethical behavior. This study examines the influence of independence and responsibility on subordinates’ obedience due to pressure from superiors to engage in unethical behavior. The research method used a true experiment using a 2 x 2 factorial design between subjects. Data was analyzed using ANOVA. The results show that subordinates who lack independence and responsibility to their superiors are more likely to engage in unethical behavior. Additionally, the results show that subordinates who lack independence and responsibility in their superiors are more likely to engage in unethical behavior. This research contributes to the behavioral research literature by understanding the factors that influence unethical behavior decisions by subordinates under pressure from superiors in real-world workplace contexts.